Etnografias Multissensoriais E Mediações Antropoéticas: A Experimentação Como Forma De Errância (2023)
ABSTRACT: In this article we make considerations related to the theoretical-methodological and practical dimensions that mobilize us as researchers of the Working Group entitled “GT AntroPoÉticas: Narratives and sensitive resonances in visual and sound images, as ways of transgressing epistemological boundaries”, linked to the Associação Latinoamericana de Antropologia (ALA) the Latin American Association of Anthropology (ALA). From an ecological perspective, we reiterate the obsolescence of the opposition between reason and sensitivity, as well as the polarity between image and text, sound and writing. From research reports carried out by the Group, we argue that experimentation conducted as a form of poetic wandering is potent both to put us in contact with the realities we wish to learn from, and to mediate the processes of communication of research results. Finally, the article shows that anthropoethical mediations constitute powerful forms of restitution of knowledge, since they offer researchers, interlocutors and the wider community a multisensory interaction, which favors the anthropological encounter.